Pozzolanic Reaction in Clayey Soils for Stabilization Purposes: A Classical Overview of Sustainable Transport Geotechnics - Onyelowe, Kennedy C.; Onyia, Michael E.; Bui Van, Duc; Baykara, Haci; Ugwu, Hyginus U. (Advances in Materials Science and Engineering, 2021)
Problematic soil stabilization processes involve the application of binders to improve the engineering properties of the soil. /is is done to change the undesirable properties of these soils to meet basic design standards. However, very little attention has been given to the reactive phase of soil stabilization. /is phase is the most important in every stabilization protocol because it embodies the reactions that lead to the bonding of the dispersed particles of clayey soil. Hence, this reactive phase is reviewed. When clayey soils which make up the greatest fraction of expansive soil come in contact with moisture, they experience volume changes due to adsorbed moisture that forms films of double diffused layer on the particles. When this happens, the clayey particles disperse and float, increasing the pore spaces or voids that exist in the soil mass. Stabilizations of these soils are conducted to close the gaps between the dispersed clayey soil particles. /is is achieved by mixing additives that will release calcium, aluminum, silicon, etc., in the presence of adsorbed moisture, and a hydration reaction occurs. /is is followed by the displacement reaction based on the metallic order in the electrochemical series. /is causes a calcination reaction, a process whereby calcium displaces the hydrogen ions of the dipole adsorbed moisture and displaces the sodium ion responsible for the swelling potential of clayey soils. /ese whole processes lead to a pozzolanic reaction, which finally forms calcium alumina-silica hydrate. /is formation is responsible for soil stabilization.
Keywords: Pozzolanic Reaction; Clayey Soils; Transport Geotechnics